2010
DOI: 10.1128/aem.03038-09
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Neurotoxin Production and Sporulation by a Putative agrBD Signaling System in Proteolytic Clostridium botulinum

Abstract: A significant number of genome sequences of Clostridium botulinum and related species have now been determined. In silico analysis of these data revealed the presence of two distinct agr loci (agr-1 and agr-2) in all group I strains, each encoding putative proteins with similarity to AgrB and AgrD of the well-studied Staphylococcus aureus agr quorum sensing system. In S. aureus, a small diffusible autoinducing peptide is generated from AgrD in a membrane-located processing event that requires AgrB. Here the ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
108
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 115 publications
(110 citation statements)
references
References 38 publications
2
108
0
Order By: Relevance
“…This also indicates the existence of complex regulatory networks modulating gene expression between these two growth phases, in agreement with the 29 genes encoding transcriptional regulators that are differentially expressed in these two conditions. Interestingly, the agrD gene, encoding an autoinducer prepeptide, was 2.5-fold induced at 10 h, suggesting that a system of quorum sensing could play a role at the end of exponential growth, as observed in several Gram-positive bacteria, including Clostridium perfringens and Clostridium botulinum (11,36). Finally, the expression of genes encoding six sigma factors (sigA2, sigB, sigH, sigF, sigE, and sigG), including 4 out of 5 sigma factors involved in the sporulation process and one sigma factor sharing similarities with SigB, which is involved in the general stress response in Gram-positive bacteria, was induced at 10 h in our transcriptome analysis, in agreement with the major changes detected in the transcriptional patterns.…”
Section: Resultsmentioning
confidence: 99%
“…This also indicates the existence of complex regulatory networks modulating gene expression between these two growth phases, in agreement with the 29 genes encoding transcriptional regulators that are differentially expressed in these two conditions. Interestingly, the agrD gene, encoding an autoinducer prepeptide, was 2.5-fold induced at 10 h, suggesting that a system of quorum sensing could play a role at the end of exponential growth, as observed in several Gram-positive bacteria, including Clostridium perfringens and Clostridium botulinum (11,36). Finally, the expression of genes encoding six sigma factors (sigA2, sigB, sigH, sigF, sigE, and sigG), including 4 out of 5 sigma factors involved in the sporulation process and one sigma factor sharing similarities with SigB, which is involved in the general stress response in Gram-positive bacteria, was induced at 10 h in our transcriptome analysis, in agreement with the major changes detected in the transcriptional patterns.…”
Section: Resultsmentioning
confidence: 99%
“…Agr-like QS systems were also recently identified in several pathogenic clostridial species, where they are similarly becoming implicated in virulence (3,5,13,21,22). For example, it was demonstrated that the Agr-like QS system is necessary for C. perfringens type C strain CN3685 to cause either necrotic enteritis or enterotoxemia in animal models (22).…”
Section: Discussionmentioning
confidence: 99%
“…Clostridium are noted to contain either single or multiple QSS, such as: (1) LuxS, (2) Agr, (3) Agr2 that are regulated by peptide signals e.g., AIP ( Table 1) [24][25][26][27][28][29]. Table 1) [30][31][32][33][34].…”
Section: Clostridiummentioning
confidence: 99%